2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944675
|View full text |Cite
|
Sign up to set email alerts
|

Statistical validation of automatic methods for hippocampus segmentation in MR images of epileptic patients

Abstract: Hippocampus segmentation is a key step in the evaluation of mesial Temporal Lobe Epilepsy (mTLE) by MR images. Several automated segmentation methods have been introduced for medical image segmentation. Because of multiple edges, missing boundaries, and shape changing along its longitudinal axis, manual outlining still remains the benchmark for hippocampus segmentation, which however, is impractical for large datasets due to time constraints. In this study, four automatic methods, namely FreeSurfer, Hammer, Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Hosseini et al provided a comprehensive evaluation of the hippocampus segmentation algorithms [Hosseini et al, ]. They categorize various metrics into three groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hosseini et al provided a comprehensive evaluation of the hippocampus segmentation algorithms [Hosseini et al, ]. They categorize various metrics into three groups.…”
Section: Introductionmentioning
confidence: 99%
“…The three groups of metrics base their evaluation on, respectively, voxel, distance, and volume. To better characterize the segmentation with and without the super resolution scheme, we also compute the evaluation metrics in [Hosseini et al, ], shown in Table .…”
Section: Introductionmentioning
confidence: 99%
“…Few reports of automated hippocampal segmentation in cases affected by mTLE have been published. 20,39,47,48 In this study, four automated methods were compared against the manual approach using 195 mTLE cases to provide a robust comparative analysis of their respective performances. Analysis of voxel-, distance-, and volume-based metrics shows that ABSS and LocalInfo are more accurate segmentation methods in the case of mTLE.…”
Section: Discussionmentioning
confidence: 99%
“…Given the current evolution in the field of automated segmentation, a modular approach to this methodology allows alternate automated segmentation methods including HAMMER, Localinfo, ANIMAL-multi, SACHA, FS+LDDMM or ABSS, 38,48,49 to be used in a similar fashion.…”
Section: A Modular Approachmentioning
confidence: 99%